2009
DOI: 10.1097/ta.0b013e31819db57c
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characterization of Comatose Patients With Cervical Spine Injury and Traumatic Brain Injury

Abstract: Patients who sustained TBI as a result of motorcycle accidents and those exhibiting a lower GCS score are at the highest risk for concomitant cervical spine injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 11 publications
3
34
1
1
Order By: Relevance
“…Examining subgroups of studies that reported the prevalence in patients with GCS 3-12 and GCS less than or equal to 8 did not reduce the heterogeneity. However, four studies reported the prevalence of concomitant cervical spinal injury in patients with TBI or head injury injured in a motor vehicle accident (MVA) [2,15,21,41]. The I 2 statistic indicated that there was only moderate heterogeneity between these studies (I 2 = 51.44%; 95% CI 0.00-83.95%).…”
Section: Cervical Spinal Injury In Tbimentioning
confidence: 99%
See 4 more Smart Citations
“…Examining subgroups of studies that reported the prevalence in patients with GCS 3-12 and GCS less than or equal to 8 did not reduce the heterogeneity. However, four studies reported the prevalence of concomitant cervical spinal injury in patients with TBI or head injury injured in a motor vehicle accident (MVA) [2,15,21,41]. The I 2 statistic indicated that there was only moderate heterogeneity between these studies (I 2 = 51.44%; 95% CI 0.00-83.95%).…”
Section: Cervical Spinal Injury In Tbimentioning
confidence: 99%
“…Eleven publications reported the prevalence of concomitant cervical spinal injury in patients with a TBI [2,12,15,21,27,28,30,33,34,37,41]. The total sample size including all studies reporting this prevalence is 573,870 patients, with sample sizes of individual studies ranging from 265 [37] to 334,864 [28].…”
Section: Cervical Spinal Injury In Tbimentioning
confidence: 99%
See 3 more Smart Citations